Temporal and Spacial Evolution of the Rainfall in the UGRH Médio Paranapanema, SP - DOI: 10.4025/actascitechnol.v31i1.3916 - Nery, Jonas Teixeira (2009)
The objective of this study was to analyze the rainfall pattern in the Unity of Gerenciamento of the Middle Paranapanema (UGRH). For so much 33 rainfall series were used in the period from 1970 to 2000. We have used different statistical parameters, such as mean, standard deviation and correlation. Also it was calculated linear correlations of the event El Niño 1982/1983, besides classification of homogeneous areas inside the basin.